ALIYAH MADRASA EDUCATION IN BANGLADESH: PROBLEMS AND PROSPECTS - Syed Mahbubul Alam Al Hasani (UIN Walisongo Semarang, 2023)
This study examines the problems and prospects of Aliya Madrasa education in Bangladesh. Education is the opportunity to enhance oneself and to develop society and the nation at large. To examine the problems and prospects of Aliya Madrasa in Bangladesh, this study employs a qualitative approach with library research and data sources from books, articles, research papers, reports of newspapers and magazines, education commissions, and government education policies. Madrasah education in Bangladesh is found to be associated with some problems from inside and outside. Through the study, some problems have been identified linked to the curriculum, management, poor funding, lack of quality teachers, shortage of instructional equipment for science subjects, and limited teacher training institutes. Furthermore, Madrasa graduates face many problems, such as university admissions examinations, government service interviews, and joining cultural activities. This paper advises that the government should consider madrasa education carefully as an important education system since it is a unique system in Bangladesh. It further suggests that the management committee, head teacher, staff, and students altogether must have to work to attain the goals of Madrasa education. Moreover, madrasa education must be restructured according to the current needs. The current curriculum approach needs to be modified and developed in accordance with the modern education system by providing all the necessary tools. Madrasas should also motivate their students to play a role in politics and take part in cultural and national activities in Bangladesh.